Incidence of a stem sitting proud of a proximally coated cementless tapered wedge stem - Kim, Chul-Ho (J Orthop Translat, 2019)
BACKGROUND/OBJECTIVE: A stem sitting proud (SP) or that above the final rasp position remains in some patients who undergo hip replacement using proximally coated tapered wedge stems. Surgeons may face challenges providing the best fit because of unpredictable SP of proximally coated tapered wedge stems. Zimmer Inc. introduced a new rasp to solve this issue but the clinical results of this rasp have not yet been published. Therefore, our aim was to address the following: (1) What is the stem SP incidence using a proximally coated cementless tapered wedge stem? (2) Does the new rasp system (0-mm rasp) improve seating height? and (3) What are the risk factors of stem SP? METHODS: We performed a retrospective study with 338 hips, in which Tri-Lock Bone Preservation Stem (BPS) was used in 181 hips and M/L Taper stem was used in 157 hips (82 hips before and 75 hips after 0-mm rasp use). A positive stem SP was defined as a stem proud height of >2 mm. We analysed and compared SP incidence in two stems and M/L Taper stems before and after the 0-mm rasp use. RESULTS: An incidence of stem SP was 13% in the Tri-Lock BPS and 15% in the M/L Taper stem before the 0-mm rasp use. Stem SP incidence in the M/L Taper stem substantially decreased after the 0-mm rasp use (4%). The significant risk factor for stem SP was use of the high offset option in Tri-Lock BPS. CONCLUSION: The proximally coated tapered wedge stems present potential problems related to stem SP. The new rasp of the M/L Taper stem showed significant improvement in initial seating height. THE TRANSLATIONAL POTENTIAL OF THIS ARTICLE: This study was conducted to understand “stem sitting proud” in proximally coated tapered wedge stem as one of the most popular designs nowadays in adult hip joint arthroplasty field. In this study, we aimed to address the incidence of stem proud, investigated the risk factor and introduced the effect of new rasp system which improve stem seating height.